ANALISIS PERAN STAKEHOLDER DALAM PENGEMBANGAN DESTINASI WISATA - Desrika Talib (Program Studi S1 Pariwisata, Universitas Muhammadiyah Gorontalo, 2020)
Stakeholders are individuals or groups who are actively involved and have a much-needed role in the sustainability of development, including tourism. The sustainability of tourism is very much determined by the active role of stakeholders in the development and management of tourist destinations. Various problems in the development of tourist destinations often occur, this can be seen from several tourist destinations that used to be visited by tourists, but are no longer considered by tourists. This study aims to examine and analyze the role of stakeholders in the development of tourist destinations by means of literature review research. Based on the results of the literature analysis that the stakeholders include; 1) Primary stakeholders (primary), 2) Supporting stakeholders (secondary), 3) Key stakeholders.